On the potential roles of phosphorus in the early evolution of energy metabolism - Nicholls, Jack W. F.; Chin, Jason P.; Williams, Tom A.; Lenton, Timothy M.; O’Flaherty, Vincent; McGrath, John W. (Frontiers in Microbiology, 2023)
Energy metabolism in extant life is centered around phosphate and the energy-dense phosphoanhydride bonds of adenosine triphosphate (ATP), a deeply conserved and ancient bioenergetic system. Yet, ATP synthesis relies on numerous complex enzymes and has an autocatalytic requirement for ATP itself. This implies the existence of evolutionarily simpler bioenergetic pathways and potentially primordial alternatives to ATP. The centrality of phosphate in modern bioenergetics, coupled with the energetic properties of phosphorylated compounds, may suggest that primordial precursors to ATP also utilized phosphate in compounds such as pyrophosphate, acetyl phosphate and polyphosphate. However, bioavailable phosphate may have been notably scarce on the early Earth, raising doubts about the roles that phosphorylated molecules might have played in the early evolution of life. A largely overlooked phosphorus redox cycle on the ancient Earth might have provided phosphorus and energy, with reduced phosphorus compounds potentially playing a key role in the early evolution of energy metabolism. Here, we speculate on the biological phosphorus compounds that may have acted as primordial energy currencies, sources of environmental energy, or sources of phosphorus for the synthesis of phosphorylated energy currencies. This review encompasses discussions on the evolutionary history of modern bioenergetics, and specifically those pathways with primordial relevance, and the geochemistry of bioavailable phosphorus on the ancient Earth. We highlight the importance of phosphorus, not only in the form of phosphate, to early biology and suggest future directions of study that may improve our understanding of the early evolution of bioenergetics. This is a provisional file, not the final typeset article principally adenosine triphosphate (ATP), are relied upon for the storage, transfer, and release of cellular energy, driving unfavorable metabolic reactions and phosphorylating metabolites. ATP is uniquely suited to its role as the 'universal energy currency' due to the highly energetic phosphoanhydride bonds (O=P-O-P=O) linking the orthophosphate anions of the triphosphate group (Westheimer, 1987). The polyanionic nature of the triphosphate group also stabilizes the nucleotide under varying physiological conditions, allowing enzymes to direct metabolic processes in specific energetic directions via hydrolysis or phosphorylation (Liu et al., 2019).